White-light driven resonant emission from a monolayer semiconductor - Shang, Jingzhi (2022)
Resonant emission in photonic structures is very useful to construct all-photonic circuits for optical interconnects and quantum computing. Optical generation of most resonant emitting modes in photonic structures has been obtained by coherent pumping rather than incoherent illumination. Particularly, the development of white-light or even solar-powered on-chip light sources remains challenging but is very attractive in view of the much facile availability of these incoherent excitation sources. Here the net resonant emission from monolayer semiconductor has been demonstrated under the simulated solar illumination by a white light-emitting diode. The device is formed by embedding a two-dimensional gain medium into a planar microcavity on a silicon wafer, which is compatible with the prevailing on-chip photonic technology. Coherent and white-light excitation sources are respectively selected for optical pumping, where the output light in two cases exhibits the well-consistent resonant wavelength, linewidth, polarization, location, and Gaussian-beam profile. The fundamental TEM00 mode behaves a doublet emission, resulting from anisotropy-induced nondegenerate states with orthogonal polarizations. The extraordinary spectral flipping is attributed to the competitive interplay of resonant absorption and emission. This work paves a way towards white-light or solar-powered state-of-the-art photonic applications at the chip scale. This article is protected by copyright. All rights reserved.